Isolation and evaluation of the antimicrobial activity of endophytic fungi from Orthosiphon aristatus - HERLAND SATRIAWAN; NIKY AFRILIA ZAIMI; ARIED ERIADI; MAI EFDI; TRINA EKAWATI TALLEI; REGINA ANDAYANI; DIAN HANDAYANI (Society for Indonesian Biodiversity, 2025)
Abstract. Satriawan H, Zaimi NA, Eriadi A, Efdi M, Tallei TE, Andayani R, Handayani D. 2025. Isolation and evaluation of the antimicrobial activity of endophytic fungi from Orthosiphon aristatus. Biodiversitas 26: 963-970. Orthosiphon aristatus, known as cat's whiskers or Javanese tea in Indonesia, has been used in traditional medicine to enhance urination, treat kidney inflammation, mitigate kidney stones, regulate diabetes, address albuminuria and syphilis, alleviate rheumatism, reduce blood glucose levels, and function as an antibacterial agent. The purpose of this study was to investigate the endophytic fungal resources of Orthosiphon aristatus and evaluate its potential as a source of bioactive compounds, particularly against antibiotic-resistant pathogens like Methicillin-resistant Staphylococcus aureus (MRSA). Eleven fungal isolates were obtained from the plant’s leaves, stems, and roots. The ethyl acetate extract of isolates was subjected to comprehensive antimicrobial screening at a concentration of 5%. Three isolates-OAA1, OAA3, and OAD1-exhibited considerable antibacterial activity, with OAD1 displaying the most significant efficacy, as evidenced by a 12.57 ± 1.09 mm inhibition zone against MRSA. Nevertheless, none of the extracts could suppress the proliferation of Candida albicans. Subsequent molecular identification verified that OAD1 was Aspergillus niger. The phytochemical analysis revealed that the triterpenoid and flavonoid groups exhibited a positive reaction, whereas the alkaloid and phenol compound groups exhibited a negative response. The findings highlight the potential of endophytic fungi from O. aristatus as promising sources of novel bioactive compounds, especially for addressing antibiotic-resistant pathogens like MRSA. The identification of A. niger as a powerful antibacterial-producing organism presents promising prospects for the creation of novel pharmaceuticals, particularly regarding multidrug-resistant infections. This study emphasizes the pressing necessity for additional research to identify and characterize the specific compounds that confer antibacterial activity and to investigate their extensive therapeutic applications.